Simplicillium pech-merlensis, a new fungal species isolated from the air of the Pech-Merle show cave - Leplat, Johann; Francois, Alexandre; Bousta, Faisl (Phytotaxa, 2021)
An original fungal strain has been recovered during an aerobiological survey in the Pech-Merle show cave (France). The use of multi-locus (ITS, LSU, SSU RPB1, RPB2 and TEF-1α) phylogenetic analysis of the strain by maximum likelihood and by Bayesian inference coupled with a morphological characterization allowed us to place it in the Simplicillium genus as Simplicillium pech-merlensis sp. nov. This new species seems morphologically close to S. calcicola and S. album, which were also first isolated from a cave habitat. This paper discusses the phylogenetic place of S. pech-merlensis and some other species in the genus Simplicillium.